2019
DOI: 10.1007/s11892-019-1152-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Information Technologies on Cardiovascular Risk Factors among Patients with Diabetes

Abstract: Purpose of Review To identify a common effect of health information technologies (HIT) on the management of cardiovascular disease (CVD) risk factors among people with type 2 diabetes (T2D) across randomized control trials (RCT). Recent Findings CVD is the most frequent cause of morbidity and mortality among patients with diabetes. HIT are effective in reducing HbA1c; however, their effect on cardiovascular risk factor management for patients with T2D has not been evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Encouraging motivated patients to prepare questions before a consultation, and to bring a companion, can increase active participation in decision-making [ 117 ]. Outside of the clinic, patient access to digital information can help to reduce the levels of CV risk factors, underscoring the importance of education [ 118 ].…”
Section: A Manifesto To Defeat Clinical Inertiamentioning
confidence: 99%
“…Encouraging motivated patients to prepare questions before a consultation, and to bring a companion, can increase active participation in decision-making [ 117 ]. Outside of the clinic, patient access to digital information can help to reduce the levels of CV risk factors, underscoring the importance of education [ 118 ].…”
Section: A Manifesto To Defeat Clinical Inertiamentioning
confidence: 99%
“…Twenty-six reviews, published between 2017 and 2020, conducted in multiple countries, were included in this umbrella review, 19-44 See Table 2. The number of studies in the selected reviews ranged from 7 to 111, and the number of participants ranged from 30 to 23,648.…”
Section: Resultsmentioning
confidence: 99%
“…19,22,25,[29][30][31][33][34][35][36][37]39,40,42 Over half of the studies assessed non-glycemic physiological outcomes (other physiological outcomes) (n = 14, 53.8%). 19,21,25,[27][28][29][30][31][32]35,38,40,43,44 The most common other physiological outcome measured was BMI (n = 8, 33.3%), [19][20][21]25,27,29,30,43 which was assessed in relation to smartphone and mobile application interventions (n = 6/8, 75.0%). 19,20,25,27,29,30 No studies assessing BMI reported statistical significance.…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation
“…However, these compounds were reported as ineffective and their application was associated with cardiovascular adverse reactions (7). Therefore, additional novel therapeutic strategies are necessary for the treatment of this disease (8). A previous study highlighted that conventional western medicine combined with traditional Chinese medicine could be used to treat DMCM (9).…”
Section: Introductionmentioning
confidence: 99%